Investigation of mercury emissions from burning of Australian eucalypt forest surface fuels using a combustion wind tunnel and field observations. (1st April 2019) - Howard, Dean; Macsween, Katrina; Edwards, Grant C.; Desservettaz, Maximilien; Guérette, Elise-Andrée; Paton-Walsh, Clare; Surawski, Nicholas C.; Sullivan, Andrew L.; Weston, Christopher; Volkova, Liubov; Powell, Jennifer; Keywood, Melita D.; et al.
Abstract: Environmental cycling of the toxic metal mercury (Hg) is ubiquitous, and still not completely understood. Volatilisation and emission of mercury from vegetation, litter and soil during burning represents a significant return pathway for previously-deposited atmospheric mercury. Rates of such emission vary widely across ecosystems as they are dependent on species-specific uptake of atmospheric mercury as well as fire return frequencies. Wildfire burning in Australia is currently thought to contribute between 1 and 5% of the global total of mercury emissions, yet no modelling efforts to date have utilised local mercury emission factors (mass of emitted mercury per mass of dry fuel) or local mercury emission ratios (ratio of emitted mercury to another emitted species, typically carbon monoxide). Here we present laboratory and field investigations into mercury emission from burning of surface fuels in dry sclerophyll forests, native to the temperate south-eastern region of Australia. From laboratory data we found that fire behaviour — in particular combustion phase — has a large influence on mercury emission and hence emission ratios. Further, emission of mercury was predominantly in gaseous form with particulate-bound mercury representing <1% of total mercury emission. Importantly, emission factors and emission ratios with respect to carbon monoxide and carbon dioxide, from both laboratory and field data all show that gaseous mercury emission from biomass burning in Australian dry sclerophyll forests is currently overestimated by around 60%. Based on these results, we recommend a mercury emission factor of 28.7 ± 8.1 μ g Hg kg −1 dry fuel, and emission ratio of gaseous elemental mercury relative to carbon monoxide of 0.58 ± 0.01 × 10 −7, for estimation of mercury release from the combustion of Australian dry sclerophyll litter. Highlights: Wildfire mercury release from eucalypt forests is currently overestimated by 60%. Under natural wildfire fuel moistures, 99% of release is elemental mercury. Fire progression impacts heavily; most mercury is released during flaming stage. Recommended emission ratio for GEM/CO is 0.58 ± 0.01 × 10 −7 .